Associations between healthcare quality and use of electronic health record functions in ambulatory care. (20th April 2015) - Ancker, Jessica S; Kern, Lisa M; Edwards, Alison; Nosal, Sarah; Stein, Daniel M; Hauser, Diane; Kaushal, Rainu; ,
Abstract: Objectives Contemporary electronic health records (EHRs) offer a wide variety of features, creating opportunities to influence healthcare quality in different ways. This study was designed to assess the relationship between physician use of individual EHR functions and healthcare quality. Materials and Methods Sixty-five providers eligible for "meaningful use" were included. Data were abstracted from office visit records during the study timeframe (183 095 visits with 61 977 patients). Three EHR functions were considered potential predictors: acceptance of best practice alerts, use of order sets, and viewing panel-level reports. Eighteen clinical quality measures from the "meaningful use" program were abstracted. Results Use of condition-specific best-practice alerts and order sets was associated with better scores on clinical quality measures capturing processes in diabetes, cancer screening, tobacco cessation, and pneumonia vaccination. For example, providers above the median in use of tobacco-related alerts had higher performance on tobacco cessation intervention metrics (median 80.6% vs. 66.7%; P < .001), and providers above the median in use of diabetes order sets had higher quality on diabetes low density lipoprotein (LDL) testing (68.2% vs. 59.5%; P == .001). Post hoc examination of the results showed that the positive associations were with measures of healthcare processes (such as rates of LDL testing), whereas there were no positive associations with measures of healthcare outcomes (such as LDL levels). Discussion Among primary care providers in the ambulatory setting using a single EHR, intensive use of certain EHR functions was associated with increased adherence to recommended care as measured by performance on electronically reported "meaningful use" quality measures. This study is relevant to current policy as it uses quality metrics constructed by contemporary certified EHR technology, and quantitative EHR use metrics rather than self-reported use. Conclusion In the early stages of the "meaningful use" program, use of specific EHR functions was associated with higher performance on healthcare process metrics.